A biometric-based system for online authentication - Ng, Shawn Wei Leung (Nanyang Technological University, 2020)
With the advancement in technology, most people can access the internet from around the world at an affordable cost. Username and Passwords have been the go-to method to secure user accounts and validate the authenticity of the user. Despite the convenience that the username and password combination has brought to authenticate users, it is not considered to be safe anymore due to the efficiency of password-cracking software which can break down your passwords in a matter of hours if the passwords are not complexed enough. Therefore, it is imperative to add an additional layer of authentication over the traditional username and password combination. In this project, the author will be exploring the use of biometrics as an additional tool to secure user accounts. The author will perform research into the various biometrics methods and focus on developing minutiae-based algorithms for fingerprints in conjunction with PCA algorithm for facial recognition for use as a biometric authentication method. MATLAB software is used for the implementation of the algorithms. The author will also assess the results of the implemented technique and attempt to incorporate the technique into a simple online system to test for its effectiveness in authenticating the user. Discussion on the successes and failures of the implementation will be performed and the author will recommend on some of the possible developments of this project in the future for future candidates to explore and complete.